PRIVATISASI SISTEM PELAYANAN KESEHATAN DAN IMPUKASINYA BAGI PERUMUSAN AGENDA PENELITIAN DAN KEBIJAKAN PUBLIK - Nasikun Nasikun (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2003)
In the face of the increasing potential of negative first generation impactsof medical industrialization and the privatization of health services in anera of globalization (i.e., increased incidence of infectious deseases andmalnutrition among the poorest poor of Indonesian population), the authorof this article proposes the imperative of finding a middle-way policy solutionto integrate the public and private systems of health services to guaranteethe provision of high quality services and the availability of accessible healthservices for the poor. After presenting a short discussion of the weaknesses ofthe public health system, he discusses the issue of medical industrializationand the privatization of health service institutions, and ends up with thepresentation of five possible alternative of health service systems at thePUSKESMAS level.